Decolonial Ecologies - Page, Joanna (Open Book Publishers, 2023)
In Decolonial Ecologies: The Reinvention of Natural History in Latin American Art, Joanna Page illuminates the ways in which contemporary artists in Latin America are reinventing historical methods of collecting, organizing, and displaying nature in order to develop new aesthetic and political perspectives on the past and the present.